PENDIDIKAN AGAMA HINDU DALAM PEMBENTUKAN KEPRIBADIAN SISWA - I Nyoman Darta (Guna Widya: Jurnal Pendidikan Hindu, 2020)
Education is not solely aimed only at teaching subjects, but educating, raising and developing a child's personality. Education is the realization of perfection that has existed in humans. So it is an integrated and harmonious development in the human personality. Education is intended to explore the potential of personality which is naturally in human beings. Lifelong education is not just for life. Education should be the process of developing a human personality as a whole, in other words the development of noble human values towards perfection and the realization of good values. Humanitarian education is not a separate lesson but must be the essence of all subjects, curriculum and extra-curricular activities.